Comparison of Continuous and Pulsating Water Jet during Piercing of Ductile Material - Nag, Akash; Srivastava, Madhulika; Petrů, Jana; Váňová, Petra; Srivastava, Ashish Kumar; Hloch, Sergej (Materials (Basel, Switzerland), 2023)
More efficient ways to process materials are constantly being sought, even in the case of continuous water flow technology, which acts on materials mainly by stagnant pressure. An alternative method is an ultrasound-stimulated pulsating water jet, the basis of which is the repeated use of impact pressure, which reduces the time interval for mechanical relaxation. This article focuses on a comparative study from the point of view of water mass flow rate on material penetration and its integrity. Relatively low pressures (p = 20, 30, and 40 MPa) with varying nozzle diameters (d = 0.4 and 0.6 mm) were used to identify the effectiveness of the pulsating water jet. The time exposure of the jet at a fixed place was varied from t = 0.5 to 5 s for each experimental condition. The results showed that with an increase in the pressure and diameter values, the disintegration depth increased. In addition, the surface topography and morphology images showed signs of ductile erosion in the form of erosion pits, upheaved surfaces, and crater formation. The microhardness study showed an increase of 10% subsurface microhardness after the action of the pulsating water jet as compared to the original material.
Keywords: erosion depth; microhardness; erosion; continuous and pulsating water jet